Can adenosine A2A receptor antagonists modify motor behavior and dyskinesia in experimental models of Parkinson's disease?. (November 2020) - Kanda, Tomoyuki; Jenner, Peter
Abstract: Current treatment of the motor symptoms of Parkinson's disease (PD) focuses on dopamine replacement therapies. While these treatments are initially highly effective, with long-term use and disease progression, the therapeutic response is often limited by the development of motor complications, dopaminergic side effects, and residual unresponsive motor and non-motor symptoms. An alternative or additive treatment approach may be to target non-dopaminergic receptors within the motor control pathways, which function to modulate basal ganglia output. Adenosine A2A receptors are one potential non-dopaminergic target as they are selectively localized to the basal ganglia and to the indirect output pathway known to modulate the striato-thalamo-cortical loops critical to the expression of the motor symptoms of PD. This paper reviews the preclinical evidence base for the ability of adenosine A2A receptor blockade to influence motor function and modulate dyskinesia expression. There is consensus that adenosine A2A receptor antagonists – administered either as a monotherapy or in combination with l -DOPA or dopamine agonists – improve motor function in both rodent and primate models of PD, and should be effective for treating the motor symptoms of PD in humans. Importantly, the improvements in motor function were seen in the absence of dyskinesia. The introduction of a non-dopaminergic approach to modifying basal ganglia function provides a useful addition to the range of available therapies for treating PD, and there is a rational basis for a drug that focuses on modifying basal ganglia output. Highlights: Long-term use of dopamine replacement therapies in Parkinson's disease is limited. Targeting a non-dopaminergic pathway may provide an alternative treatment strategy. A2A antagonists show promise in treating the motor symptoms of PD.